The Effect of Organizational Communication Towards Resistance to Change: A Case Study in Banking Sector - Betül Akan; Funda Er Ülker; Agah Sinan Ünsar (Economic Review: Journal of Economics and Business, 2016)
Resistance to change is a significant factor that has a direct effect on change efforts. If the employees are well-informed about the organizational change process, and if their opinions are asked regarding the decisions to be taken in explanation of the change process, the employees would adopt the change process and it would help breaking their resistance to change. Accordingly, it is aimed in this study to analyze the influence of organizational communication on resistance to change. Recent studies may accept that effective organizational communication is one of the primary determinants of resistance to change. In line with the purpose of the study, data have been collected through questionnaire method from 406 state and private bank employees in Marmara Region (Turkey).The data obtained have been analyzed through exploratory factor analysis, correlation analysis and Mann- Whitney U difference test. Multiple regression analysis has also been made in order to explain the characteristics of the relations, which have been determined through correlation analysis. According to the results of the research, a positive, but insignificant relationship has been observed between goal setting and critical communication, which are the two sub- dimensions of resistance to change and organizational communication. It has been observed that a very insignificant part of the variability in employees' resistance to change levels has been explained through goal- setting and critical communication. In has also bee observed that private bank employees resist more to change than state bank employees.
Keywords: M10; 330; Organizational Communication; Change; Resistance; Banking Sector